Korelasi Antara Motivasi, Strategi Belajar, dan Prestasi Akademik Taruna ATKP Makassar: Tinjauan Belajar Level 4 Standard ICAO - Rossydi, Ahmad; Erna Wahyu P., Agnes; Atbar, Mustahrim (Airman: Jurnal Teknik dan Keselamatan Transportasi, 2018)
This research aimed at finding out the correlation among learning strategies, motivation, and academic achievement of CASEA Makassar cadet: a review of ICAO standard level 4. The research employed quantitative research. The sample of this research were Air Traffic Controller and Flight Communication cadet of CASEA Makassar. The cadets were chosen by applying cluster random sampling technique. Data collection by using the questionnaire instrument. Data analysis was done using correlation analysis Product Moment of Pearson. On the significance level of 5%, The findings of the research reveal that: (1) the motivation of learning has positive correlation against learning strategies with a value r of 0.851. (2) The motivation of learning has a positive correlation with the cadet academic achievement that in the study of these is English proficiency with value r of 0.892. (3) Language learning Strategies have a positive correlation with academic achievement (English proficiency) with value r of 0.802. Motivation as a giver of stimulus while learning strategies were directing and maximize the push positive. Motivation rose up the confidence which is very important in the development of English language proficiency. Learning strategies can control production limitations of language.